Exploring Guardians’ Perceptions towards Edutainment Environments: The Case of Kidzania, Cairo, Egypt - Mennatalla Mostafa A. Salama; Manal S. Abou El-Ela; Marwa H. Khalil (Buildings, 2022)
Over the last few decades, the concept of combining education and entertainment has become increasingly popular. Edutainment (education and entertainment) environments started appearing in 1970 and have expanded, ever since, across the globe. This study seeks to explore the perception of guardians towards the edutainment experience and its impact on their children, with special reference to Kidzania’s branch in Cairo, Egypt. The study adopted an interpretive qualitative approach that combines different data gathering methods, including informal discussions, in-depth semi-structured interviews, on-site sketches, observation, field notes, photographs, and archival sources. The number of guardians involved in the study was 12, accompanying 23 children. A thematic analysis of the data revealed two important overarching themes: qualities of the edutainment environment, and the factors affecting the interaction between guardians and children. The first theme, qualities of the edutainment environment, includes three categories: safe environment, exploratory environment, and well-maintained environment. The second theme, factors affecting the interaction between guardians and children, encompasses three categories: physical proximity, visual connectivity, and provision of basic amenities. The findings of the study were discussed in light of relevant previous accounts and studies. In its conclusion, the study confirms that such edutainment environments can be considered as significant informal educational play settings in which children learn valuable life skills, complementing those learned in formal learning environments. Such findings are expected to provide useful insights that could inform different initiatives aiming to create thriving edutainment centers and engaging informal learning environments.